Sijmon Andries Valckenaer: An Amsterdam Silversmith in the Spirit of Paul van Vianen - Biemond, Dirk Jan (The Rijksmuseum Bulletin, 2023)
Dirk Jan Biemond emphasizes the influence of the sculptural artistry of Paul van Vianen in silversmithing; for instance, the Amsterdam silversmith Sijmon Andries Valckenaer (1609-1672) worked in the same spirit.